Contribution of coherent structures to momentum and concentration fluxes over a flat vegetation canopy modelled in a wind tunnel. (April 2015) - Conan, Boris; Aubrun, Sandrine; Coudour, Bruno; Chetehouna, Khaled; Garo, Jean-Pierre
Abstract: Coherent structures dominate the shear flow in and above the vegetation canopy, affecting the transport of passive scalars. Their detailed understanding is therefore of great interest for a number of environmental studies such as organic gas exchange, pollution dispersion, or forest fire propagation. In the present study, a forest embedded in an atmospheric boundary layer was reproduced in a wind tunnel. An area source was installed to mimic the volatile organic compounds emission coming from the vegetation. A fast gas analyser combined to a triple hot-wire anemometer were used to measure simultaneously and at the same point the momentum and the concentration fluxes above the canopy. This particular set-up enabled the complex scalar exchange mechanism to be studied in the well defined and stationary boundary conditions of a laboratory experiment simulating neutral atmospheric conditions. Measurements showed that the contribution of coherent structures to the momentum and the concentration flux was 80% and 60% respectively. Contributions were found to be nearly constant with height. The combination of velocity and concentration measurements enabled the determination of the mean concentration of the coherent structures. Results highlights the preponderant role of ejections in releasing highly concentrated gas pockets above the forest canopy. These releases were measured to be, in average, 40% more concentrated than the average gas concentration at the same height. It is shown that 70% of the extreme events observed are linked to an ejection process. Highlights: A forest canopy is modelled in an atmospheric boundary layer wind tunnel. Volatile Organic Compounds emission is reproduced. Momentum and concentration fluxes are measured simultaneously. The contribution of coherent structures to concentration flux is strong. Ejection process is responsible for high gas concentration releases.